2021
DOI: 10.1177/0020764020988572
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological effects of the Coronavirus (Sars-CoV-2) imposed lockdown on vulnerable patients in treatment in a mental health outpatient department for migrants and individuals in poor socioeconomic conditions

Abstract: Background: The effects of Sars-Cov-2 pandemic may increase vulnerability of migrants. Aims: To investigate the effects of the governmental lockdown on the mental health of vulnerable migrants in treatment at an outpatient department. Method: In a telephone survey post-migration living difficulties and psychopathological symptoms were investigated, particularly post-traumatic thoughts and nightmares, anxiety, depression, feelings of tension and irritability, other sleep problems, as well as COVID-19 related fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In one French study, the prevalence of depression increased (72% vs. 65%) [ 37 ]. Symptoms also worsened among undocumented migrants in Italy (50% worsened anxiety, 38% worsened depression) [ 25 ] and the U.S. (49% worsened anxiety, 46% worsened depression) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one French study, the prevalence of depression increased (72% vs. 65%) [ 37 ]. Symptoms also worsened among undocumented migrants in Italy (50% worsened anxiety, 38% worsened depression) [ 25 ] and the U.S. (49% worsened anxiety, 46% worsened depression) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mental health of asylum seekers and undocumented migrants was further compromised by reduced access and use of health services during the pandemic. For instance, fewer undocumented migrants visited a free psychiatric clinic for migrants in Italy, with only 17.5% returning for follow-up treatment during the peak of the pandemic [ 26 ] and 32% discontinuing psychopharmacological treatment [ 25 ]. A similar pattern was observed in another general Italian clinic, with women experiencing the sharpest decline (77%) in visits [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that migrants are more likely of being young [ 1 , 2 ] and at increased risk for SARS-COV-2 infection [ 2 ]. In addition to language as barrier to quality of care access in the emergence room [ 3 ], mental health has been of concern among migrants worldwide [ 4 - 6 ]. The continuous arrival of migrant in this region makes hard contact tracing of positive cases.…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 99%
“…In this context, multiple studies have indicated elevated rates of depression and anxiety in Middle Eastern countries hosting Syrian refugees during the pandemic, including Jordan (Al-Ajlouni et al, 2020 ; Naser et al, 2020 ) and Lebanon (Hajjar & Abu-Sittah, 2021 ). There is also initial evidence that refugees are experiencing marked anxiety and mood problems during the pandemic (Aragona et al, 2021 ; Hajjar & Abu-Sittah, 2021 ).…”
Section: Introductionmentioning
confidence: 99%